PTH-118 Mucosal tissue short chain fatty acids contribute to prediction of pouchitis in restorative proctocolectomy. (June 2019) - Segal, Jonathan; Sarafian, Magali; Pechlivanis, Alexandros; Serrano Contreras, Ivan Jose; Brignardello, Jerusa; Siaw, Yih-harn; Braz, Lucia; Clark, Susan; Holmes, Elaine; Hart, Ailsa
Abstract : Background: Restorative proctocolectomy is a surgical option in patients with ulcerative colitis who become refractory to medical therapy. Short chain fatty acids (SCFA) are organic fatty acids with 1–6 carbons which arise from bacterial metabolism from carbohydrates entering the colon. Various studies have implicated SCFA in both the development of IBD and flares of IBD. Furthermore, it has been shown that SCFA concentrations are significantly lower in faecal samples from patients with pouchitis when compared with healthy controls. Our study aimed to assess longitudinal changes in SCFA that occur in a pouch to determine if they can predict or are associated with the development of pouchitis. To date no study has analysed short chain fatty acids in mucosal biopsy tissue from these patients. Methods: Patients who underwent restorative proctocolectomy at a single centre underwent pouchoscopy at the time of restoration of continuity and then every 6 months for a year. Biopsies from the pouch were retrieved from the pouch body. Pouchitis was defined using the pouch disease activity index. The development of pouchitis was assessed at months 6 and 12 months. Biopsies samples were snap frozen at time of biopsy and stored in -80°C. Samples were thawed and weighed. Sterile water and Methyl tertiary-butyl ether with internal standard (IS) were added with a ratio of 20 mg of sample:50µL of H20:250µL of MTBE and IS with a further 4µL of hydrochloric acid added to each sample. 30µL of the polar phase was then placed into silanized Eppendorf tubes. 150µL of derivatiser was added to each sample and the cap of the tube applied immediately. These were then incubated for 45 minutes at 60°C in an oven. 70µL from the silanised vial was placed into vial inserts and analysed in the gas chromatography mass spectrometry machine. (GC-MS). SCFA were measured using an Agilent 7000C Triple Quadrupole GC/MS-MS System according to a previously published method. Simca was used for multivariate analysis and T-tests were used for univariate analysis. Results: There were 56 biopsy samples. There were 22 patients (17 males); 16 UC and 6 FAP patients with longitudinal follow up. The median age of the cohort was 40 years (range 20–60 years). Of the UC patients four developed pouchitis within one year. When comparing UC patients at the time of closure of ileostomy, there were there were significant decreases in caproic acid (4674µM vs 12217µM p<0.01), valeric acid (1580µM vs 3695µM p=0.01), isovolaric acid (721µM vs 2940µM p=0.05), isobutyric acid 35072µM vs 76074µM p=0.03) and lactic acid (1580µM vs 3732µM p=0.02) between those who developed pouchitis within a year and those who did not develop pouchitis at 1 year.There were no significant differences detected between UC patients and FAP patients at each time point analysis. Conclusion: The study has suggested that a decrease in SCFA found in the mucosal tissue at time of closure of ileostomy may predict onset of pouchitis within a year. This study is the first to demonstrate that SCFA can be analysed from biopsies. Future studies need to determine factors that may contribute to tissue SCFA levels which may help develop a potential therapeutic target to optimise and potentially reduce the incidence of pouchitis.